Impact of topographic internal lee wave drag on an eddying global ocean model. (January 2016) - Trossman, David S.; Arbic, Brian K.; Richman, James G.; Garner, Stephen T.; Jayne, Steven R.; Wallcraft, Alan J.
Highlights: Large changes in the abyss, small changes near the surface with wave drag. Deflection by topographic blocking can lead to increases in abyssal kinetic energy. Adding wave drag does not go to the detriment of model performance. Momentum flux should be distributed heterogeneously throughout water column. Abstract: The impact of topographic internal lee wave drag (wave drag hereafter) on several aspects of the low-frequency circulation in a high-resolution global ocean model forced by winds and air-sea buoyancy fluxes is examined here. The HYbrid Coordinate Ocean Model (HYCOM) is run at two different horizontal resolutions (one nominally 1/12° and the other 1/25°). Wave drag, which parameterizes both topographic blocking and the generation of lee waves arising from geostrophic flow impinging upon rough topography, is inserted into the simulations as they run. The parameterization used here affects the momentum equations and hence the structure of eddy kinetic energy. Lee waves also have implications for diapycnal mixing in the ocean, though the parameterization does not directly modify the density. Total near-bottom energy dissipation due to wave drag and quadratic bottom boundary layer drag is nearly doubled, and the energy dissipation due to quadratic bottom drag is reduced by about a factor of two, in simulations with an inserted wave drag compared to simulations having only quadratic bottom drag. With the insertion of wave drag, the kinetic energy is reduced in the abyss and in a three-dimensional global integral. Deflection by partial topographic blocking is inferred to be one reason why the near-bottom kinetic energy can increase in locations where there is little change in dissipation by quadratic bottom drag. Despite large changes seen in the abyss, the changes that occur near the sea surface are relatively small upon insertion of wave drag into the simulations. Both the sea surface height variance and geostrophic surface kinetic energy are reduced on global average by more than twice the seasonal variability in these diagnostics. Alterations in the intensified jet positions brought about by inserting wave drag are not distinguishable from the temporal variability of jet positions. Various statistical measures suggest that applying wave drag only within a fixed distance from the seafloor is not detrimental to the model performance relative to observations. However, the introduction of a novel diagnostic suggests that one way to improve the wave drag parameterization is to allow the vertical deposition of lee wave momentum flux to be spatially heterogeneous.